2023
DOI: 10.1002/ejoc.202300656
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Chiroptical Properties of Binaphthyl‐Hinged [5]Helicenes

Abstract: The synthesis, structure, and circularly polarized luminescence (CPL) of two types of shape‐persistent [5]helicenes, hinged by a tethered (−OCH2CH2O−) or untethered (−OCH3) binaphthyl, are reported. The binaphthyl tethering system facilitated an effective Wittig ring‐closure reaction in the synthesis of a macrocyclic precursor, which could be easily converted to the title compound via successive photocyclization. The tethered groups were replaced with untethered −OCH3 groups by treatment with BBr3 followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Recently, we synthesized chiral macrocycles 37a,b, in which helicenes were combined with tethered binaphthyl, based on the fact that binaphthyl induces chirality (Figure 14). 85 [5]-Helicene slowly racemizes at room temperature. 86,87 In 2004, Marinetti et al reported that a chiral 1,3pentandiol tether at the end of [5]-helicene prevents epimerization and induces chirality in the helicene moiety.…”
Section: Binaphthyl-hinged [5]-helicenementioning
confidence: 99%
“…Recently, we synthesized chiral macrocycles 37a,b, in which helicenes were combined with tethered binaphthyl, based on the fact that binaphthyl induces chirality (Figure 14). 85 [5]-Helicene slowly racemizes at room temperature. 86,87 In 2004, Marinetti et al reported that a chiral 1,3pentandiol tether at the end of [5]-helicene prevents epimerization and induces chirality in the helicene moiety.…”
Section: Binaphthyl-hinged [5]-helicenementioning
confidence: 99%
“…Effective strategies to overcome this limitation include converting the naphthalene ring to a larger  system, such as a pyrene ring [12][13][14] , and enhancing the  system by introducing a phenylethynyl group onto the naphthalene ring [15] . Recently, many studies on the use of compounds linked to the binaphthyl skeleton as chiral luminescent molecules, including molecules with circularly polarized luminescence (CPL), have been reported [16][17][18][19][20] . In this study, a series of compounds (denoted 3-PE to 8-PE) was synthesized, involving the bridging of the two hydroxy groups of 1,1ʹ-bi-2-naphthol (BINOL) by a methylene unit (i.e., one carbon atom) and the incorporation of two phenylethynyl groups at all of the feasible substitution positions.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Recently, many studies on the use of compounds linked to the binaphthyl skeleton as chiral luminescent molecules, including molecules with circularly polarized luminescence (CPL), have been reported. [16][17][18][19][20] In this study, a series of compounds (denoted 3-PE to 8-PE) was synthesized, involving the bridging of the two hydroxy groups of 1,1'-bi-2-naphthol (BINOL) by a methylene unit (i. e., one carbon atom) and the incorporation of two phenylethynyl groups at all of the feasible substitution positions. Subsequently, compounds possessing four or six phenylethynyl groups (3,6-PE, 4,6-PE, 5,6-PE, 6,7-PE, and 3,4,6-PE) were also synthesized, and their optical properties were systematically evaluated (Figure 1).…”
Section: Introductionmentioning
confidence: 99%